Sv. Jurij at Legen (Slovenia) – early medieval church and graveyard - Modrijan, Zvezdana; Strmčnik Gulič Mira (Arheološki vestnik, 2020)
During the research inside the present-day filial church of St George (Sv. Jurij) at Legen near Slovenj Gradec, remains of an early medieval church and graveyard were discovered. The early medieval church has a rectangular ground plan with a semi-circular apse on the eastern side, which is enclosed on the exterior side in a rectangular form, and an entrance hall on the western side. A contemporary graveyard is spread around it. Most of the graves were discovered within the present-day church. The early medieval graves were badly damaged during the construction of the Romanesque church, with its later reconstructions, and medieval and modern age burials. Nevertheless, certain grave units and individual items enable the dating of the church and graveyard surrounding it into the time of the last third of the 9th and especially into the 10th century. The predecessor of St George is thus one of the rare researched stone churches from this period in the area of the South-Eastern Alps.